Dynamics and stability analysis of enzymatic cooperative chemical reactions in biological systems with time-delayed effects - Jan A.; Shah R.A.; Bilal H.; Almohsen B.; Jan R.; Sharma B.K. (Elsevier B.V., 2025)
The mathematical modeling and dynamic analysis of time-delayed enzymatic chemical reactions in biological systems are presented in this research. The objective is to examine the function of time lags in these reactions and to get a complete knowledge of the behavior of biological systems in a reaction to modifications in the quantity present of reactants and products. The model, which is based on delay differential equations, includes a time delay term to account for the lag between changes in the concentration of reactants, reaction rate constants and product responses. The findings give insight into how enzymatic processes behave dynamically and how stability is impacted by time lags, oscillation and general efficiency of the system. These results have significant importance for our comprehension of how biological processes are regulated and for the creation of biological control structures. ? 2024 The Author(s)